PENGARUH STRUKTUR MODAL TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN - Muhammad Faried Pratama; Dedy Takdir Syaifuddin; Salma Saleh (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
The research objective is to examine and examine the effect of capital structure on corporate value in consumer companies listed on the Indonesia Stock Exchange. The analysis model used is the structural equation model. The number of companies studied was 26 companies with the 2013-2017 observation year. The method of determining the research sample using the purpose sampling method based on the criteria of consumer companies listed on the Indonesia Stock Exchange during the observation period from 2013-2014.The results of the study found that: 1). Capital structure has a significant effect on profitability 2). Profitability has a significant effect on firm value, 3). Capital structure has an effect on company value mediated by profitability.Keywords: capital structure, profitability and company value